Evaluation of La0.6Sr0.4Co0.2Fe0.8O3-δ as a potential cathode for proton-conducting solid oxide fuel cell - Ismariza Ismail,; Nafisah Osman,; Abdul Mutalib Md Jani, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The application of La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) as a potential cathode working on a BaCe0.54Zr0.36Y0.1O2.95 (BCZY) electrolyte for proton conducting solid oxide fuel cell was investigated. LSCF nanoceramic powders were synthesized by an activated carbon-assisted sol-gel process using metal nitrate-based chemicals. The LSCF powder was transformed to a slurry and spin-coated onto both surfaces of BCZY pellet to form a symmetrical cell with the configuration of LSCF|BCZY|LSCF. The symmetrical cell was subsequently sintered at 950°C for 2 h to allow a good contact formation between electrode/ electrolyte layers. The phase structural verification of the calcined powders was investigated by X-Ray diffractometer (XRD). Field-emission scanning electron microscopy (FESEM) was employed to examine the morphology of the sintered cell. The electrochemical behaviour of the symmetrical cell was studied by an electrochemical impedance spectroscopy. The formation of a single perovskite LSCF phase with a crystallite size of 20 nm was obtained at 700°C as corroborated by XRD analysis. The FESEM images showed a good contact between LSCF cathode and BCZY electrolyte at electrode/ electrolyte interfacial layer. The ASR obtained for LSCF symmetrical cell measured at 700°C with and without Pt current collector is 0.87 and 31.25 Ωcm2, respectively.